Strategic site selection for biohydrogen production: Enhancing rural sustainability through agricultural biomass - Seyhan, Mehmet; Tanurun, Himmet Erdi; Aydin, Nezir; Ayyildiz, Ertugrul (ELSEVIER, 2025)
This study develops a systematic multi-criteria decision-making framework to identify optimal sites for biomassbased hydrogen production facilities, emphasizing sustainability and rural development in developing countries. We introduce a hybrid Multi-Criteria Decision-Making (MCDM) approach that integrates the Best-Worst Method (BWM) for criteria weighting with Pythagorean Fuzzy COmbinative Distance-based ASsessment (PF-CODAS) for alternative ranking, enabling robust evaluation under uncertainty. The criteria are structured as a five-pillar framework consisting of economic market factors, environmental sustainability, resource utilization, process efficiency, and safety considerations, operationalized via 29 sub-criteria and informed by seven domain experts. Applying this approach in T & uuml;rkiye, five rural locations (Konya, Adana, Bal & imath;kesir, S,anl & imath;urfa, Samsun) were assessed, using agricultural residues as the primary feedstock context. Konya ranked first and Adana second, reflecting strong logistics and market conditions and biomass availability alongside environmental performance. BWM results highlight GHG Emission Reduction as the highest weighted sub-criterion with Water Resource Utilization, and within process efficiency, Thermal Optimization is also prominent. A sensitivity analysis showed stable rankings for the top alternative, and comparative benchmarking against two well-known methods yielded consistent top two results, underscoring methodological robustness. This study highlights the significant potential of strategically located biomass-to-hydrogen facilities to improve rural livelihoods, support local economies, and contribute to global sustainability goals by offering a viable alternative to traditional biomass use.
Keywords: Rural development; Biohydrogen; Agricultural residues; Site selection; Multi-criteria decision making; Best-worst method; HYDROGEN-PRODUCTION; SOCIAL SUSTAINABILITY; STEAM GASIFICATION; RENEWABLE ENERGY; CODAS; PLANT; Science & Technology - Other Topics; Energy & Fuels